Construction programming by line-of-balance method / Suhaina Baharudin - Baharudin, Suhaina (1984)
Construction Programming by Line-of-Balance Method is a technique developed by U.S. Navy Department in 1942 which was then applied for the programming and control of repetitive building in National Building Agency of Great Britain. The effectiveness of the control provided in a repetitive situation, provides a precise measurement in which to measure their performance. To illustrate the application of Line-of-Balance Method, this project deals with the construction of 196 units Two- Storey, low rise medium cost houses constructed by the P.K.N.S. at Section 17, Shah Alam. Throughout this project, the objectives which the programme seeks to show are :- (1) how it is intended to carry the contract work. (2) the relationships or sequence between the different operations. (3) the time span during which an operation can be carried out highlighting, if possible, the critical operations, and duration. (4) the plant and labour requirement for each operations. So far there is no information of the usage of Line-of- Balance Method for the construction planning of engineering activities of repetitive nature in Malaysia. It should be noted that this study is concerned to only one project. The writer does not have sufficient site experience in order to handle this work with excellent judgement. However attempt is made here.